Studi Pendahuluan Pada Upaya Pengembangan Laboratorium Virtual bagi Calon Guru Fisika - Gunawan Gunawan; Ahmad Harjono; Hairunnisyah Sahidu (Department of Physics Education, Universitas Mataram, 2015)
The purpose of this study was to develop a model of virtual labs on some concepts of physics. In this article will describe some of the findings of the preliminary study carried out in the framework of the development of the virtual laboratory model. Data were collected through observation, questionnaires, interviews, and studies related documents. The results showed that a number of problems related to the lecture held, particularly with respect to the selection method of teaching on certain concepts, issues related to the activities of laboratory experiments, the description of the physics of matter that is difficult for students. Results of this study are expected to be the basis for the development of the model as well as efforts to improve the quality of learning physics, particularly for prospective teachers of physics.